Produção de carvão ativado a partir de endocarpo de coco da baía (Cocos nucifera) aplicado ao processo de adsorção do herbicida metribuzin - Mangueira, Erivone Soedja Veriato (2014)
In this work activated carbons were prepared cononut endocarp (Cocos nucifera) as a material precursor where aluminum sulphate was the activating chemical agent and water vapor the physical one. The chemical and textural characteristics and its application in the removal of the herbicide metribuzin were evaluated and compared with other types of activated carbon through adsorption isotherm tests. The samples were activated with different concentrations of chemical activating agent and carbonized at 780 °C. The activated carbon had a surface area of approximately 610 m2.g lower than the commercial coal and physico-chemically activated charcoal with steam and phosphoric acid, which were used as a comparative sample. All carbons were characterized by the determination of moisture, ash, pH, specific surface area BET, scanning electronic microscopy (SEM) and adsorption kinetics essays to achieve maximum adsorption of the herbicide. The equilibrium removal of metribuzin was expressed as adsorption isotherms, and the experimental data had fitted better regarding to Freundlich model. Kinetic experiments were performed to verify the required time for equilibrium, which were achieved about 30 to 36 hours. Regarding to the kinetic models studied, the best model proposed to the adsorbents was the pseudo-second order. The ability of the studied adsorbents was proportional to the surface area, micropore volume, and also more alkaline nature of the surface, in view of the greater affinity with charcoal metribuzin basic surfaces. The adsorption capacities of activated carbons followed the order: CAFQ 4:1 > CACarb > CAFQ 3:1 > 2:1 CAFQ > CAAcF when applying 48 hours of adsorption